MALFORMASI VENA VERUKOSA: PERKEMBANGAN DIAGNOSIS DAN TATA LAKSANA (Media Dermato Venereologica Indonesiana, 2022)
Verrucous venous malformation (VVM), formerly known as verrucous hemangioma, is a rare, congenital, non-hereditary vascular malformation. The initial clinical manifestations of VVM include bluish patches that become erythematous to purplish, then enlarge slowly to become verrucous and hyperkeratotic papules, plaques, or nodules. Its etiopathogenesis remain unknown. It used to be one of unclassified vascular anomalies due to its clinical feature consistent with malformations, but shows positive results on immunohistochemical for tumors. The identification of somatic mutations in the mitogen-activated protein kinase 3 (MAP3K3) gene has classified it into venous malformation group. Clinically this lesion often resembles other diseases that may lead to misdiagnosis. Investigations such as dermoscopy, radiology, histopathology, and immunohistochemical are continually updated as new cases are found. Superficial ablative procedures often result in recurrence of the lesions. There is potential for targeted therapy using sirolimus but surgical excision remain preferred choice. Early diagnosis and prompt treatment are important due to the risk of recurrence.